PENGARUH TERAPI CUPPING TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN FROZEN SHOULDER - Joko Tri Haryanto; Purwanto; Chusnul Zulaika; Eka Deviany Widyawaty (Jurnal Medicare, 2026)
Background: Frozen shoulder is a musculoskeletal disorder characterized by shoulder pain and restricted range of motion caused by inflammation and fibrosis of the joint capsule. This condition may reduce functional ability and quality of life. Cupping therapy has been widely used as a complementary treatment for pain management; however, evidence regarding its effectiveness in patients with frozen shoulder remains limited. Objective: To analyze the effect of cupping therapy on pain intensity reduction in patients with frozen shoulder. Methods: This study employed a pre-experimental one-group pretest-posttest design. A total of 16 patients with frozen shoulder were recruited using purposive sampling. Pain intensity was measured before and after cupping therapy using a standardized pain assessment instrument. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of 95% (α = 0.05). Results: The mean pain score before cupping therapy was 66.56 ± 25.82, while the mean pain score after therapy decreased to 37.44 ± 21.51. The average reduction in pain score was 29.13 ± 8.94 points. The Wilcoxon Signed Rank Test showed a p-value of 0.00043 (p < 0.05), indicating a statistically significant difference between pre- and post-treatment pain scores. Conclusion: Cupping therapy significantly reduces pain intensity in patients with frozen shoulder. Therefore, cupping therapy may be considered a complementary non-pharmacological intervention for pain management in patients with frozen shoulder.